Efficacy of transdermal diclofenac patch and ketoprofen patch as postoperative analgesia after extraction of first premolars bilaterally in both arches for orthodontic purpose: A comparative study - Daya Shankar; Abhishek Sinha; Santosh Anand; Neeraj Verma; Shivendra Choudhary (Journal of Pharmacy and Bioallied Sciences, 2021)
Aim: The aim of the study was to compare the efficacy of transdermal diclofenac patch with ketoprofen patch as postoperative analgesia after extraction of first premolars bilaterally in both arches for orthodontic purpose. Materials and Methods: A split-mouth technique was used in 52 patients with the age group of 15–25 years for extracting maxillary and mandibular first premolars bilaterally for orthodontic reason. A single ketoprofen patch was used after the extraction of premolars from first and fourth quadrant, whereas for the extraction of second and third quadrant premolars, diclofenac patch was used. All the extractions were performed under local anesthesia. The data were compiled and statistically analyzed using the student's t-test. Results: Mean visual analog scale score for diclofenac and ketoprofen patch was 2.05 (0.75) and 1.09 (0.3), respectively. Thirteen patients required additional medication (25%) and 1 (1.9%) patient with diclofenac and ketoprofen patch, respectively. No major complication or adverse effects were observed in any of the groups. Conclusion: Both diclofenac and ketoprofen transdermal patches are helpful in relieving pain after orthodontic extraction. Patients with diclofenac patch required more additional analgesia within 24 h compared to that with ketoprofen patch. None of the drugs showed any significant adverse effects and were well tolerated by the patients.